Klausula Eksonerasi Pada Perjanjian Pinjam Meminjam Uang Dalam Layanan Pinjaman Online (Fintech Peer To Peer Lending) - Dewi Ariyani, Novi (Universitas Jambi, Fakultas Hukum, 2023)
This study aims to discuss legal issues, namely the void of norms because POJK No.77/POJK.01/2016 concerning information technology-based money-lending services with the terms and conditions of fintech p2p lending providers are not in line with their practices and can cause legal problems because there is no protection. law for lenders in the practice of online lending and borrowing money services so that it can lead to legal conflicts and the absence of legal certainty or special rules regarding the transfer of responsibility from the organizer, of course, is quite detrimental to its users (lenders). Based on the issues studied, the authors use a type of normative legal research which studies legal materials, both primary and secondary legal materials. Normative research places law as a system of norms because this type of research looks at aspects of understanding a legal norm contained in a law and norms that live and develop in society. The nature of the research used is analytical descriptive, the author tries to describe events and incidents that are the center of attention without giving special treatment to these events. The Consumer Protection Law prohibits the inclusion of exoneration clauses related to information technology-based money lending and borrowing agreements, but OJK provisions do not explicitly regulate the legal consequences of including exoneration clauses so that there is a void in norms and can lead to legal conflicts so that harmonization of these norms is necessary.